POEMS Syndrome - Rare Paraneoplastic Syndrome in a Young Female - Prusty, B Saroj Kumar; Ramineni, Kiran Kumar; Reddy G, Krishna Mohan; Reddy, G Vamshi Krishna; Momin, Majed Abdul Basit (Journal of Medicine, 2019)
POEMS syndrome is defined by the presence of peripheral neuropathy (P), organomegaly (O), endocrinopathy (E), a monoclonal plasma cell disorder (M) and skin changes (S). We report a case of POEMS syndrome in a 34-year-old female who presented with three month history of back pain, pain in lower limbs, weakness, numbness and edema in both lower limbs. Patient was unable to walk and bed ridden with worsening general condition, shortness of breath and fever for three days. Further clinical examinations (hyperpigmentation), systemic examination (hepato-splenomegaly), laboratory investigation (hypothyroidism), CT showed sclerosis in sacral bone and left acetabular lytic lesion, which on biopsy and immunohistochemistry showed plasma cell dyscrasia and confirmed by increased plasma cells in bone marrow biopsy and presence of M band in immunofixation study. Here we describe, in detail, an unusual clinical presentation of this rare paraneoplastic syndrome with multisystemic involvement which needs multidisciplinary approach with strong clinico-pathological & radiological correlation to diagnose this rare entity. J MEDICINE JAN 2020; 21 (1) : 55-58